Xanthomatous Posttraumatic Fibro-Osseous Lesion of the Rib: A Rare and Underrecognized Entity. Case Report and Literature Review. (October 2017) - Nassereddine, Hussein; Larousserie, Frédérique; Campagna, Raphaël; Castier, Yves; Couvelard, Anne; Choudat, Laurence; Sannier, Aurélie
Posttraumatic fibro-osseous lesion (PTFOL) is a rare lesion that typically affects the ribs and is probably a posttraumatic reactive process. Because PTFOL is often misdiagnosed as fibrous dysplasia, osteoid osteoma, benign fibrous histiocytoma or rib metastases, chest wall resection, leading to a significant morbidity, is the main treatment modality. We report the case of a 30-year-old male patient with no history of previous trauma presenting with chest pain. Computed tomography scan showed an eighth left rib well-defined ovoid and hypodense lesion with circumferential sclerotic margin and no cortical breakthrough. Posterolateral thoracotomy was performed and a histological diagnosis of xanthomatous posttraumatic fibro-osseous lesion of the rib was made. PTFOL is a benign lesion that should be recognized to avoid unnecessary surgical treatment and complications. We provide a summary of clinical, histopathological, and radiological aspects of PTFOL and discuss differential diagnoses.